Scour depth, sediment characteristics, and hydrodynamic conditions dataset at British offshore wind farms, 2005-2014 - Karen Garcia; Christian Jordan; Gregor Melling; Alexander Schendel; Mario Welzel; Torsten Schlurmann (PANGAEA, 2025)
This dataset provides calculated scour depth and associated site-specific environmental parameters from multiple British offshore wind farms (OWFs). Information from OWFs in both the Irish Sea and the North Sea is included in the dataset, and a range of hydrodynamic regimes and seabed conditions are covered. Scour depth was extracted from pre- and post-construction bathymetries, conducted between 2005 and 2014, and refers to the vertical seabed change around the OWES. This dataset collection contains processed data on scour depth, sediment properties, and hydrodynamic conditions at multiple offshore wind energy structures (OWES) across nine British offshore wind farms (OWFs). Scour depth values were derived from the difference between pre- and post-construction multibeam bathymetric datasets. Sediment grain size information was obtained from publicly available benthic reports from Marine Data Exchange (MDE). Hydrodynamic conditions were reconstructed using one-year hindcast time series data before the post-bathymetry date, and extreme conditions were represented by the 99th percentiles by the Copernicus Marine Service (CMEMS).